2009
DOI: 10.1016/j.taap.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the inhibition of human butyrylcholinesterase and acetylcholinesterase by the organophosphate chlorpyrifos oxon

Abstract: Acetylcholinesterase (EC 3.1.1.7) and butyrylcholinesterase (EC 3.1.1.8) are enzymes that belong to the superfamily of α/β-hydrolase fold proteins. While they share many characteristics, they also possess many important differences. For example, whereas they have about 54% amino acid sequence identity, the active site gorge of acetylcholinesterase is considerably smaller than that of butyrylcholinesterase. Moreover, both have been shown to display simple and complex kinetic mechanisms, depending on the particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 45 publications
(88 reference statements)
0
31
0
Order By: Relevance
“…The enzyme acetylcholinesterase (AChE, EC 3.1.1.7) plays a major role in the regulation of several physiological events, and the activity of the cholinergic system is vital to normal behavior and muscular function (Schetinger et al, 2000;Payne et al, 1996). As such, the crucial role of this enzyme in neural transmission makes it a primary target for a large number of cholinesterase-inhibiting drugs and toxins (Pohanka, 2011), and a valuable diagnostic tool for verifying exposure to chemical agents (Shenouda, Green, Sultatos, 2009). The heme pathway enzyme deltaaminolevulinate dehydratase (δ-ALA-D, EC 4.2.1.24) presents high sensitivity to pro-oxidant situations, and to impairment of metabolic processes, thus being used to evaluate toxicity as well (Nogueira et al, 2003;Souza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme acetylcholinesterase (AChE, EC 3.1.1.7) plays a major role in the regulation of several physiological events, and the activity of the cholinergic system is vital to normal behavior and muscular function (Schetinger et al, 2000;Payne et al, 1996). As such, the crucial role of this enzyme in neural transmission makes it a primary target for a large number of cholinesterase-inhibiting drugs and toxins (Pohanka, 2011), and a valuable diagnostic tool for verifying exposure to chemical agents (Shenouda, Green, Sultatos, 2009). The heme pathway enzyme deltaaminolevulinate dehydratase (δ-ALA-D, EC 4.2.1.24) presents high sensitivity to pro-oxidant situations, and to impairment of metabolic processes, thus being used to evaluate toxicity as well (Nogueira et al, 2003;Souza et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of toxic action, similarly to other phosphoroorganic substaces, mainly results from inhibition of enzymes from the group of esterases i.e. : acetylcholinesterases and butyrylcholinesterases (Amitai et al 1998, Shenouda et al 2009). One to the action of enzymes, mainly cytochrome P450, chlorpyrifos is converted to an oxygen analoque -chlorpyrifos oxone, which acts more strongly in comparison with maternal substance -chlorpyrifos (Sams et al 2004, Mutch andWilliams 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, in the present study, methamidophos enantiomers showed a different behavior for plasma BChE in hens, because the (þ)-methamidophos presented an IC50 lower than (À)-methamidophos. This inversion between inhibition of two a/b hydrolyses with 54% of identical amino acid sequence [36] may be explained by the fact that the active site gorge of BChE is higher than that of AChE [37]. Thus, it is possible to say that the results of enantiomers inhibition on esterases are not easily extrapolated from one hydrolyse to another.…”
Section: Butyrylcholinesterasementioning
confidence: 99%